On the use of nonlocal regularisation in slope stability problems. (February 2017) - Summersgill, F.C.; Kontoe, S.; Potts, D.M.
Abstract: This study examines the use of nonlocal regularisation in a coupled consolidation problem of an excavated slope in a strain softening material. The nonlocal model reduces significantly the mesh dependency of cut slope analyses for a range of mesh layouts and element sizes in comparison to the conventional local approach. The nonlocal analyses are not entirely mesh independent, but the predicted response is much more consistent compared to the one predicted by local analyses. Additional Factor of Safety analyses show that for drained conditions the nonlocal regularisation eliminates the mesh dependence shown by the conventional local model.